2016
DOI: 10.1097/aln.0000000000000919
|View full text |Cite
|
Sign up to set email alerts
|

JM25-1, a Lidocaine Analog Combining Airway Relaxant and Antiinflammatory Properties

Abstract: Background Inhaled lidocaine antagonized bronchospasm in animal models and patients, but adverse effects limited its efficacy. This study evaluated the antibronchospasm potential of the analog JM25-1, exploring in vitro mechanisms and translation to an animal model. Methods The effectiveness of JM25-1 was assessed in GH3 cells, rat tracheal rings, mouse lymphocytes, and human eosinophil systems in vitro, assessing changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 38 publications
4
25
0
Order By: Relevance
“…We found that intranasal administration of PPC inhibited goblet cell infiltration in the nasal mucosa of mouse model of allergic rhinitis. This finding was in concordance with a recent study which found that a lidocaine analog significantly inhibited OVAinduced mucus secretion in mice [18]. A different study found that topical application of lidocaine inhibited mucous secretion [19].…”
Section: Discussionsupporting
confidence: 82%
“…We found that intranasal administration of PPC inhibited goblet cell infiltration in the nasal mucosa of mouse model of allergic rhinitis. This finding was in concordance with a recent study which found that a lidocaine analog significantly inhibited OVAinduced mucus secretion in mice [18]. A different study found that topical application of lidocaine inhibited mucous secretion [19].…”
Section: Discussionsupporting
confidence: 82%
“…Commercial enzyme immunosorbent assay (ELISA) kits were used for the measurement of cytokine and chemokine proteins in whole-lung homogenates and cell-free supernatants as reported (38). Briefly, lung tissue was homogenized on ice using a tissue homogeneizer (Omni International, Kennesaw, GA, USA) in 1 ml PBS containing 0.05% Triton X-100 and a protease inhibitor cocktail (Hoffmann-La Roche, Basel, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…[9] Here-in, we present how transition metal-catalyzed ester activation can be exploited to couple avery broad range of methyl esters with amines,a voiding the substantial scope limitations of existing systems.Asimple Ni 0 catalyst is used, providing high functional group tolerance and producing methanol as the only stoichiometric by-product. Most importantly,n on-nucleophilic aniline derivatives,w hich typically require pre-treatment with aggressive base prior to reaction with esters,c ould be used without any modification of the conditions (13)(14)(15)(16)(17)(18). We began by investigating the reaction of methyl benzoate with aselection of metals,ligands,and nucleophiles that had proven effective in previous catalytic coupling reactions that require cleavage of strong C À Obonds ( Figure S1).…”
mentioning
confidence: 99%
“…[12] With ester activation, methyl chloroacetate can instead be used to first substitute at the a-carbon and then diversify the amide component by Ni-catalyzed coupling.This strategy was used to more efficiently access lidocaine derivatives 46-48 and JM25-1, [13] ar ecently discovered potential bronchospasm therapeutic (Scheme 4b). The orthogonality of using am etal to activate esters was investigated via reactions with methyl 4-fluorobenzoate 41.T raditional S N Ar reactions were achieved when using DMSO as as olvent (42, 43), while amide bond formation occurred selectively in toluene with the Ni catalyst (44, 45)( Scheme 4a).…”
mentioning
confidence: 99%
See 1 more Smart Citation